PENGARUH SISTEM PENYALURAN KREDIT TERHADAP KEPUASAN ANGGOTA CREDIT UNION KARYA MURNI MEDAN - Saragih, Nawary (Jurnal Manajemen dan Bisnis, 2018)
Credit Union (CU) Karya Murni Medan is a business engaged in lending and receiving deposits. Members of the CU often complain because of the vulnerable process of administering credit until the disbursement phase, resulting in members less satisfied with the credit distribution system set by the CU. From the problem identification, formulated the research problem is "Does the credit channeling system have a significant influence on the satisfaction of CU members" .The research hypothesis "Is there any effect of credit distribution system on the satisfaction of CU members". The purpose of this study is to determine the effect of credit distribution system on the satisfaction of CU members. The benefits of research is to increase insight and knowledge of the author on the influence of credit distribution system to the satisfaction of CU members. The study population is all members of CUtahun 2016 as many as 7200 people. The sample was taken 96 people with maximum error sampling. Data collection techniques are documentation techniques and questionnaires. Data analysis technique used is simple linear regression analysis.Conclusion: The credit disbursement system in CU has not been optimally satisfying the members, due to the length of time span between applications with credit realization. The credit interest rate offered is higher than other CU. Members of CU complain that they are not responding quickly enough to complain, if the application is approved, it is obliged to pay the administrative fee. The equations are y = 0.727 + 0.803.x. That is, the credit channeling system has a positive effect on the satisfaction of CU members. The correlation coefficient value is 0.769. That is, the credit channeling system has a positive relationship to the satisfaction of CU members. Determinant coefficient value of 0,591, meaning that member satisfaction can be explained by credit distribution system equal to 59,1% while 40,9% again explained by other factor. The test results z-count = 11.646> z table = 0,000, then H0 is rejected. That is, the credit channeling system has a significant effect on the satisfaction of CU members, can be accepted at a significance level of 5%. Suggestion as information material. Instead, CU will accelerate the decision making of credit realization, to maintain member loyalty. Preferably, CU decreases loan interest rates in anticipation of the shift of members to other CUs that offer lower interest rates. To increase member satisfaction, CU should waive members on the credit administration costs . Because satisfaction on credit distribution system there are other factors as much as 40.9%, then CU Management should be in overcoming it requires system improvement and service improvement in various fields.